The Influence of Vitamin E to Protect Myocard Damage Due to the High Fat Diet - Yanuartono Yanuartono; Dhirgo Adji (Indonesian Food and Nutrition Progress, 2002)
Eighteen male rats, strain Sprague Dawley, were used as experimental animals to study the protective effects of vitamin E on the incidence of myocard damage due to high fat diet. The rats were randomly alloted into 3 groups of six each. All of the rats were treated high fat diet. Group I as control was fed diet containing high fat. Group II was fed containing 30 IU of vitamin E, and group III was fed containing 180 IU of vitamin E. After 60 days, the blood sample were collected from the hearts for detected specific heart protein by troponin T analysis. The statistical analysis for cardiac troponin data showed that there were no significant differences between group I and group II . However, there were significant differences between group I and group III or between group II and group Ill. This result indicated that vitamin E have some effect to protect myocard damage from group III (p 0,05) that containing 30 IU of vitamin E.